1991
DOI: 10.1128/iai.59.10.3439-3445.1991
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous gamma interferon-independent host resistance against Listeria monocytogenes infection in CD4+ T cell- and asialo GM1+ cell-depleted mice

Abstract: The effects of in vivo administration of antibodies against T-cell subsets and asialo GM1 (ASGM1)-bearing ceUs on endogenous gamma interferon (IFN-,y) production and host defense in Listeria monocytogenes-infected mice were investigated. Endogenous IFN-y titers in the bloodstreams and spleen extracts of mice on day 2 of infection were partially suppressed by administration of rabbit anti-ASGM1 antibody, but not by anti-CD4 monoclonal antibody (MAb) or anti-CD8 MAb. Of the different combinations of these three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 18 publications
(22 reference statements)
1
27
0
Order By: Relevance
“…IFN-Q production ceased just before mice died. IFN-Q is reportedly produced mainly by natural killer (NK) cells early in L. monocytogenes infection [11,35,36]. We con¢rmed that endogenous IFN-Q production induced by lethal L. monocytogenes infection in C57BL/6 mice was abolished when the mice were pretreated with anti-asialo GM1 antibody or anti-NK1.1 mAb (data not shown), presuming that NK cells might be dysfunctional or might be depleted before death from listeriosis.…”
Section: Discussionmentioning
confidence: 90%
“…IFN-Q production ceased just before mice died. IFN-Q is reportedly produced mainly by natural killer (NK) cells early in L. monocytogenes infection [11,35,36]. We con¢rmed that endogenous IFN-Q production induced by lethal L. monocytogenes infection in C57BL/6 mice was abolished when the mice were pretreated with anti-asialo GM1 antibody or anti-NK1.1 mAb (data not shown), presuming that NK cells might be dysfunctional or might be depleted before death from listeriosis.…”
Section: Discussionmentioning
confidence: 90%
“…In a sublethal infection with L. monocytogenes, conversion from the sublethal infection to the lethal infection was not observed in CD8 + cell-depleted mice, although antilisterial resistance was markedly suppressed in these animals [21,28,29]. Alternatively, depletion of CD4 + cells showed little effect on antilisterial resistance [21,28,29]. Furthermore, studies using severe combined immunodeficiency mutant mice showed that host resistance to L. monocytogenes infection could be expressed in the presence of endogenous cytokines such as TNF and IFN-y [30,31].…”
Section: Anti-tcrmentioning
confidence: 99%
“…Evaluation of in vivo cell depletion has been shown previously (Nakane and Minagawa, 1984;Nakane et al, 1991;Hiromatsu et al, 1992).…”
Section: In Vivo Depletion Of Cd3 + Cells Cd4 + Cells Cd8 + Cells mentioning
confidence: 99%
“…helping immune reaction, cytotoxicity to infected cells, and secretion of cytokines (Ertl et al, 1989;Lindsley et al, 1991;Nakane et al, 1991). CD4 ÷ T lymphocytes secrete cytokines (Nakane et al, 1991) and show helper activities (Ertl et al, 1989). CD8 ÷ lymphocytes act as cytotoxic T lymphocytes (CTL) and destroy virus-infected cells (Lindsley et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation